Analisis Faktor-Faktor yang Mempengaruhi Kemiskinan di Provinsi Sulawesi Tenggara - Nurul Humaera; Muhammad Ghafur Wibowo; Muhammad Wakhid Musthofa (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
This study aims to analyze the factors that affect the prevalence of poverty in Southeast Sulawesi Province during the period 2014 to 2023. The independent variables studied include the Open Unemployment Rate (TPT), Human Development Index (HDI), and Total Population (JP), with poverty level as a dependent variable. The method used is multiple linear regression analysis using the Ordinary Least Squares (OLS) method processed with E-Views software. The results of the study show that simultaneously, TPT, HDI, and JP have a significant influence on the poverty rate in Southeast Sulawesi. However, when tested partially or individually, the findings showed different results. Only the Population (JP) variable has been proven to have a significant and meaningful impact on the poverty rate in the region. In contrast, the Open Unemployment Rate (TPT) and the Human Development Index (HDI) did not show a significant influence separately on the dependent variables. This research presents an important contribution in deconstructing the complexity of the relationship between key socio-economic factors and the determination of poverty rates in Southeast Sulawesi province, as well as underlining the importance of population control in poverty alleviation efforts in the region.